Profil Pengelolaan Obat Golongan Narkotika, Psikotropika dan Prekursor di Apotek Rumah Sakit Stella Maris Makassar - SAFITRI, INDAH DIAN; Hasrawati, Andi; Amirah, Sitti (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Drug management is a major factor in supporting the patient's recovery rate. Drug management can run well if supported by the ability of existing resources, both in pharmacies, health centers, and hospitals. Narcotics, psychotropic drugs and precursors can affect the nervous system and legally their circulation has been regulated in legislation. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2015, the management of narcotic drugs, psychotropic drugs and precursors consists of circulation, storage, destruction, and recording and reporting. This study aims to determine the drug management process at the Stella Maris Makassar Hospital Pharmacy. This study uses a qualitative method with a descriptive approach and data collection techniques through interviews and observations. The results of this study are in the process of circulation, destruction, and recording and reporting at the Stella Maris Makassar Hospital Pharmacy according to the guttman scale obtained a percentage of 100% with a very good scale. However, in the storage process there are still some discrepancies so that the percentage obtained is 85%. This has met the applicable regulatory standards in Indonesia and is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No. 3 of 2015.